“Project Expose”- Radiotherapy Advocacy in the Hospital - Nurses Do It Best! - Dominguez, Christine; Marriott, Amanda; Fogarty, Gerald B (Archives of Clinical and Medical Case Reports, 2018)
Introduction: Better radiotherapy (RT) modalities and techniques with efficacy proven in prospective trials have led to an increase the indications for RT. In our own large Australian metropolitan tertiary referral hospital however, general staff and students have little appreciation of this. Advocacy is needed for this effective intervention to become more known and accessible. Method: We launched “Project Expose”, an educational intervention aimed at the general hospital staff. The main component was a guided tour of our department where all radiation craft groups explained what they do, while showing how the radiation machines function. We wanted to measure the outcome of this intervention. Results: 500 were invited, 350 invitations were distributed, 45 attended (45/350 - 13%). Of these, 10 responded to an invitation that accompanied a purpose designed business card, 8 were by word of mouth from those who had previously attended. 14 had been encouraged by an educator to attend. 32/45 (71%) completed the post tour survey. Of these, 11 were nurses, 9 were allied health, 7 were health care students, 4 were non-health occupation or students, and 1 was medical staff. 97% of survey respondents said their knowledge about modern radiotherapy had increased. Discussion: The tour was not a success in that it was difficult to attract general hospital staff (13%). The intervention was a success for those that attended, with 97% of survey completers said they had increased in knowledge of modern radiotherapy. An important finding was the pivotal a role of nurses in radiotherapy advocacy.